A flexible asymmetric composite thermal conductive film and its preparation method and application

By using graphene oxide and hexagonal boron nitride as thermal conductivity in the flexible thermal conductivity film, combined with polyvinyl alcohol and organic molecular modifier, a flexible asymmetric composite thermal conductivity film with high thermal conductivity and good insulation properties was prepared, which solved the problem of difficulty in taking into account both thermal conductivity and insulation properties in the prior art.

CN116640396BActive Publication Date: 2025-03-25HUAQIAO UNIVERSITY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310621665.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-30
Publication Date
2025-03-25
Estimated Expiration
2043-05-30

Smart Images

  • Figure CN116640396B_ABST
    Figure CN116640396B_ABST
Patent Text Reader

Abstract

The present invention provides a flexible asymmetric composite thermally conductive film and a preparation method and application thereof, belonging to the technical field of thermal conductive materials. The flexible asymmetric composite thermally conductive film provided by the present invention uses polyvinyl alcohol as a polymer matrix, which can make the composite film have good flexibility and insulation properties. The present invention uses graphene oxide and hexagonal boron nitride as two-component thermally conductive fillers. Due to the different densities of different thermally conductive fillers, the upper layer of the composite film is brown in color, with more graphene oxide gathered, and the lower layer is white in color, with more hexagonal boron nitride gathered. The two sides of the obtained composite thermally conductive film have obvious differences in color, micromorphology, thermal conductivity and electrical conductivity. In the present invention, hexagonal boron nitride can form a good thermal conductive network pathway through precipitation self-assembly during the film forming process, which is beneficial to the improvement of the thermal conductivity of the composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heat-conducting materials, and in particular to a flexible asymmetric composite heat-conducting film and a preparation method and application thereof. Background Art

[0002] The rapid development of 5G communications, 5G high-power chips, and the development of foldable displays and full-screen displays have led to a sharp increase in the heat generated by terminal devices. The continuous accumulation of heat will affect the reliability and safety of electronic equipment. How to achieve efficient heat dissipation is an urgent problem to be solved. Compared with traditional thermal management materials, flexible thermally conductive film materials with high in-plane thermal conductivity have attracted great interest from researchers in the past decade and have shown great potential in thermal management applications of next-generation devices. Flexible thermally conductive film materials have ultra-high in-plane thermal conductivity and excellent flexibility. When used as a film radiator, they can evenly transfer the heat from a point heat source to a large surface area, and then use large-area thermal convection and thermal radiation to dissipate heat.

[0003] At present, flexible thermal conductive films mainly include full carbon thermal conductive films and polymer thermal conductive films. Although full carbon thermal conductive films have high thermal conductivity, they also have good electrical conductivity, which cannot meet the requirements of material insulation and thermal conductivity in some special occasions. Although pure polymers have good electrical insulation properties, their thermal conductivity is extremely low. In order to prepare high thermal conductive films that meet heat dissipation requirements, it is often necessary to adjust their molecular chain structure. The preparation process is extremely complex and costly, making it difficult to apply in practice. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a flexible asymmetric composite thermally conductive film and a preparation method and application thereof. The flexible asymmetric composite thermally conductive film provided by the present invention has good thermal conductivity on the basis of good insulation performance, and the electrical conductivity and thermal conductivity on both sides of the composite film are asymmetric.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a flexible asymmetric composite thermally conductive film, comprising the following components in parts by weight:

[0007]

[0008]

[0009] The total mass content of the graphene oxide and the hexagonal boron nitride in the flexible asymmetric composite thermal conductive film is 10-30%.

[0010] Preferably, the degree of polymerization of the polyvinyl alcohol is 1500-2400, and the degree of alcoholysis is 77-99%.

[0011] Preferably, the graphene oxide sheet has a thickness of 0.8 to 1 nm;

[0012] The hexagonal boron nitride has a sheet diameter of 1 to 2 μm and a sheet thickness of 1 to 2 nm.

[0013] Preferably, the organic molecule modifier is one or more of tannic acid, dodecyl glucoside and dopamine.

[0014] Preferably, the thickness of the flexible asymmetric composite thermally conductive film is 30-120 μm.

[0015] The present invention provides a method for preparing the above-mentioned flexible asymmetric composite thermally conductive film, comprising the following steps:

[0016] Mixing polyvinyl alcohol, glycerol and water to obtain a polyvinyl alcohol solution;

[0017] Mixing hexagonal boron nitride, an organic molecular modifier and water to obtain a modifier / hexagonal boron nitride mixed solution;

[0018] Mixing the graphene oxide dispersion with the modifier / hexagonal boron nitride mixed solution to obtain a graphene oxide / modifier / hexagonal boron nitride mixed solution;

[0019] The polyvinyl alcohol solution and the graphene oxide / modifier / hexagonal boron nitride mixed solution are mixed to obtain a film-forming solution;

[0020] The film-forming liquid is scraped on the surface of the substrate, and the obtained wet film is left to stand and heated to dry, so as to obtain a flexible asymmetric composite thermally conductive film.

[0021] Preferably, the mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 7 to 10%;

[0022] The mass concentration of hexagonal boron nitride in the modifier / hexagonal boron nitride mixed solution is 55-67%;

[0023] The mass concentration of the graphene oxide dispersion is 0.7-1.6%.

[0024] Preferably, the scraping speed is 160-220 mm / s; the standing temperature is 25-40° C., and the time is 1-2 h.

[0025] Preferably, the heating and drying comprises a first heating stage and a second heating stage which are performed sequentially, wherein the temperature of the first heating stage is 25-40°C and the time is 2-5 hours; the temperature of the second heating stage is 60-80°C and the time is 8-12 hours.

[0026] The present invention provides application of the flexible asymmetric composite thermally conductive film in flexible electronic devices.

[0027] The present invention provides a flexible asymmetric composite thermally conductive film, comprising the following components in parts by mass: 4-5 parts of polyvinyl alcohol; 0.1-1 parts of glycerol; 0.1-0.8 parts of graphene oxide; 0.3-1 parts of organic molecular modifier; 1.2-2 parts of hexagonal boron nitride; the total content of the graphene oxide and hexagonal boron nitride in the asymmetric thermally conductive film is 10-30%. The flexible asymmetric composite thermally conductive film provided by the present invention uses polyvinyl alcohol as a polymer matrix, which can make the composite film have good flexibility and electrical insulation properties. The present invention uses graphene oxide and hexagonal boron nitride as two-component thermally conductive fillers. Due to the different densities of different thermally conductive fillers, the upper layer of the composite film is brown in color, with more graphene oxide gathered, and the lower layer is white in color, with more hexagonal boron nitride gathered. In the present invention, the oxygen-containing functional groups such as hydroxyl and carboxyl on the surface of graphene oxide enable it to be well dispersed in a water-soluble polymer matrix, which can reduce the interfacial thermal resistance effect caused by poor compatibility between the filler and the polymer matrix and weak interfacial bonding; hexagonal boron nitride can form a good thermal conductive network pathway through precipitation self-assembly during the film formation process, which is beneficial to the improvement of the thermal conductivity of the composite film. In the present invention, the organic molecular modifier and hexagonal boron nitride can be adsorbed on the surface of hexagonal boron nitride through hydrogen bonding, giving hexagonal boron nitride surface activity, so that hexagonal boron nitride can form a good interface bonding with the matrix. In the present invention, graphene oxide and hexagonal boron nitride have similar phonon scattering spectra, which can synergistically improve the thermal conductivity and mechanical properties of the composite film, and there are obvious differences in color, micromorphology, thermal conductivity and electrical conductivity on both sides of the composite thermal conductive film, which can be used in special scenarios, such as flexible electronic skin.

[0028] The present invention provides a method for preparing the above-mentioned flexible asymmetric composite thermally conductive film. The present invention controls the order of adding raw materials, first adds an organic molecule modifier as a foaming agent, and provides a bubble template for the filler hexagonal boron nitride; adding graphene oxide is to stabilize and fix the bubble template, so that the filler is distributed around the bubble to form a 3D interconnected filler network structure; the present invention adopts a scraping film method to form a film, and under the action of the scraper shear force, the thermally conductive filler will form a horizontal orientation in the polymer matrix; during the heating and drying process, as the water solvent evaporates, the hexagonal boron nitride will self-assemble to form a network that is crisscrossed horizontally and vertically, thereby forming a good thermal conductive network path in the matrix, thereby improving the thermal conductivity of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a SEM image of hexagonal boron nitride in Example 1;

[0030] Figure 2 The surface morphology and SEM image of the composite film in Example 1;

[0031] Figure 3 is a cross-sectional SEM image of the composite film in Example 1;

[0032] Figure 4 This is a diagram showing the flexibility of the composite film in Example 1;

[0033] Figure 5 This is a surface SEM image of the composite film after etching in Example 1;

[0034] Figure 6 The thermal conductivity diagram of the graphene oxide surface of the composite thin film obtained in Examples 1 to 4 and Comparative Examples 1 to 4;

[0035] Figure 7 The thermal conductivity diagram of the boron nitride surface of the composite thin film obtained in Examples 1 to 4 and Comparative Examples 1 to 4;

[0036] Figure 8 The thermal conductivity diagram of the graphene oxide surface and the boron nitride surface of the composite film obtained in Example 3 after reduction;

[0037] Fig. 9 Surface resistance of the graphene oxide surface and the boron nitride surface of the composite film obtained in Example 3 after reduction. DETAILED DESCRIPTION

[0038] The present invention provides a flexible asymmetric composite thermally conductive film, comprising the following components in parts by weight:

[0039]

[0040] The total mass content of the graphene oxide and the hexagonal boron nitride in the flexible asymmetric composite thermal conductive film is 10-30%.

[0041] Unless otherwise specified, the raw materials used in the present invention are all commercially available.

[0042] In terms of parts by mass, the flexible asymmetric composite thermally conductive film provided by the present invention includes 4 to 5 parts of polyvinyl alcohol, preferably 4.2 to 4.8 parts, and more preferably 4.5 parts. In the present invention, the degree of polymerization of the polyvinyl alcohol is preferably 1500 to 2400, and more preferably 1800 to 2200; the degree of alcoholysis is preferably 77 to 99%, and more preferably 80 to 90%. Polyvinyl alcohol is an environmentally friendly water-soluble polymer with good film-forming properties. The formed film is transparent, strong, and soft, and has higher physical properties such as tensile strength and wear resistance than other resin materials. The present invention uses polyvinyl alcohol as the raw material of the composite thermally conductive film, which can make the composite film have good flexibility.

[0043] Based on the mass fraction of the polyvinyl alcohol, the flexible asymmetric composite thermally conductive film provided by the present invention comprises 0.1 to 1 part of glycerol, more preferably 0.5 part. In the present invention, the glycerol acts as a plasticizer.

[0044] Based on the mass fraction of the polyvinyl alcohol, the flexible asymmetric composite thermally conductive film provided by the present invention includes 0.1 to 0.8 parts of graphene oxide, preferably 0.2 to 0.6 parts, and more preferably 0.3 to 0.5 parts. In the present invention, the thickness of the graphene oxide sheet is preferably 0.8 to 1 nm. In the present invention, the oxygen-containing functional groups such as hydroxyl and carboxyl on the surface of graphene oxide enable it to be well dispersed in the water-soluble polymer matrix, which can reduce the interfacial thermal resistance effect caused by the poor compatibility of the filler with the polymer matrix and the weak interface bonding.

[0045] Based on the mass fraction of the polyvinyl alcohol, the flexible asymmetric composite thermally conductive film provided by the present invention includes 0.3 to 1 parts of an organic molecule modifier, preferably 0.5 to 0.8 parts. In the present invention, the organic molecule modifier is preferably one or more of tannic acid, dodecyl glucoside and dopamine. In the present invention, the organic molecule modifier and hexagonal boron nitride can be adsorbed on the surface of hexagonal boron nitride through hydrogen bonding, giving the hexagonal boron nitride surface activity, so that the hexagonal boron nitride can form a good interface bond with the substrate.

[0046] Based on the mass fraction of the polyvinyl alcohol, the flexible asymmetric composite thermally conductive film provided by the present invention includes 1.2 to 2 parts of hexagonal boron nitride, preferably 1.4 to 1.8 parts, and more preferably 1.5 to 1.6 parts. In the present invention, the sheet diameter of the hexagonal boron nitride is preferably 1 to 2 μm, more preferably 1.5 μm; the sheet thickness is preferably 1 to 2 nm, more preferably 1.5 nm. In the present invention, the hexagonal boron nitride can form a good thermal conductive network pathway through precipitation self-assembly during the film formation process, which is beneficial to the improvement of the thermal conductivity of the composite film.

[0047] In the present invention, the total mass content of the graphene oxide and hexagonal boron nitride in the flexible asymmetric composite thermally conductive film is 10-30%, preferably 15-25%, and more preferably 20%.

[0048] In the present invention, the thickness of the flexible asymmetric composite thermally conductive film is preferably 30 to 120 μm, more preferably 50 to 100 μm.

[0049] The present invention provides a method for preparing the above-mentioned flexible asymmetric composite thermally conductive film, comprising the following steps:

[0050] Mixing polyvinyl alcohol, glycerol and water to obtain a polyvinyl alcohol solution;

[0051] Mixing hexagonal boron nitride, an organic molecular modifier and water to obtain a modifier / hexagonal boron nitride mixed solution;

[0052] Mixing the graphene oxide dispersion with the modifier / hexagonal boron nitride mixed solution to obtain a graphene oxide / modifier / hexagonal boron nitride mixed solution;

[0053] The polyvinyl alcohol solution and the graphene oxide / modifier / hexagonal boron nitride mixed solution are mixed to obtain a film-forming solution;

[0054] The film-forming liquid is scraped on the surface of the substrate, and the obtained wet film is left to stand and heated to dry, so as to obtain a flexible asymmetric composite thermally conductive film.

[0055] The present invention mixes polyvinyl alcohol, glycerol and water to obtain a polyvinyl alcohol solution. In the present invention, the present invention has no special requirements for the mixing method, as long as the polyvinyl alcohol solution is a uniform and transparent solution. In the present invention, the mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution is preferably 7-10%, more preferably 8-9%.

[0056] The present invention mixes hexagonal boron nitride, an organic molecule modifier and water to obtain a modifier / hexagonal boron nitride mixed solution. In the present invention, the mixing method is preferably stirring and mixing, and the mixing time is preferably 4 to 12 hours, more preferably 6 to 10 hours. In the present invention, the mass concentration of hexagonal boron nitride in the modifier / hexagonal boron nitride mixed solution is preferably 55 to 67%, more preferably 58 to 65%.

[0057] The present invention mixes a graphene oxide dispersion with the modifier / hexagonal boron nitride mixed solution to obtain a graphene oxide / modifier / hexagonal boron nitride mixed solution. In the present invention, the mass concentration of the graphene oxide dispersion is preferably 0.7-1.6%, more preferably 1-1.3%. The present invention does not specifically specify the source of the graphene oxide dispersion, and a conventional commercially available graphene oxide dispersion in the art or a self-prepared one can be used. In the present invention, the mixing preferably includes ultrasonic mixing and magnetic stirring mixing performed sequentially, the frequency of the ultrasonic mixing is preferably 19.5kHz, and the time is preferably 10-30min; the rotation speed of the magnetic stirring mixing is preferably 300-600r / min, and the time is preferably 4-10h.

[0058] The present invention mixes the polyvinyl alcohol solution and the graphene oxide / modifier / hexagonal boron nitride mixed solution to obtain a membrane-forming solution. In the present invention, the mixing preferably includes ultrasonic mixing and magnetic stirring mixing performed in sequence, the frequency of the ultrasonic mixing is preferably 19.5kHz, and the time is preferably 10 to 30 minutes; the speed of the magnetic stirring mixing is preferably 300 to 600 r / min, and the time is preferably 4 to 10 hours.

[0059] The present invention scrapes the film-forming liquid on the surface of the substrate, and the obtained wet film is left to stand and heated to dry to obtain a flexible asymmetric composite thermally conductive film. The present invention preferably uses an automatic film coating machine to scrape the film. In the present invention, the scraping speed is preferably 160 to 220 mm / s, and more preferably 180 to 200 mm / s.

[0060] In the present invention, the standing temperature is preferably 25 to 40° C., and the standing time is preferably 1 to 2 hours, more preferably 1.5 hours.

[0061] The present invention preferably performs the heating and drying in a constant temperature box. In the present invention, the heating and drying includes a first heating stage and a second heating stage performed sequentially, the temperature of the first heating stage is preferably 40°C, and the time is preferably 5 hours; the temperature of the second heating stage is preferably 60°C, and the time is preferably 12 hours; the present invention can improve the flexibility of the composite film through the segmented heating.

[0062] The present invention adopts a scraping method to form a film, and under the action of the scraper shear force, the thermal conductive filler will form a horizontal orientation in the polymer matrix; during the heating and drying process, as the water solvent evaporates, the hexagonal boron nitride will self-assemble to form a horizontal and vertical crisscross network, thereby forming a good thermal conductive network path in the matrix, thereby improving the thermal conductivity of the composite material.

[0063] The present invention provides application of the flexible asymmetric composite thermally conductive film in an electronic display screen.

[0064] The flexible asymmetric composite thermally conductive film provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0065] Example 1

[0066] (1) 9 g of polyvinyl alcohol particles (degree of polymerization: 1700, degree of alcoholysis: 88%) were dispersed in 90 mL of deionized water and magnetically stirred at room temperature until the solution was uniform and transparent. Then, 1 g of glycerol was added and magnetically stirred in a 90° C. warm water bath for 2 h to obtain a polyvinyl alcohol solution;

[0067] (2) mixing 1.5 g of hexagonal boron nitride having a sheet thickness of 1 to 2 μm, 1 g of dodecyl glucoside, and 20 mL of deionized water under magnetic stirring at room temperature to obtain a dodecyl glucoside / hexagonal boron nitride mixed solution;

[0068] (3) 50 mL of a graphene oxide dispersion having a mass concentration of 1.0 wt% was mixed with the modifier / hexagonal boron nitride solution obtained in step (2), first dispersed under high-frequency ultrasound for 30 min, and then magnetically stirred at room temperature for 6 h to obtain a uniformly dispersed graphene oxide / dodecyl glucoside / hexagonal boron nitride mixed solution;

[0069] (4) 50 mL of the polyvinyl alcohol solution obtained in step (1) and the mixed solution obtained in step (3) were first dispersed under high-frequency ultrasound for 2 minutes, and then magnetically stirred for 6 hours at room temperature to mix evenly to obtain a polyvinyl alcohol / graphene oxide / dodecyl glucoside / hexagonal boron nitride mixed solution;

[0070] (5) The polyvinyl alcohol / graphene oxide / dodecyl glucoside / hexagonal boron nitride mixed solution is poured onto a stainless steel plate, and a film is scraped with an automatic coating machine at room temperature. The film is first kept at a constant temperature of 40°C for 5 hours, and then placed in a constant temperature box at 60°C for drying for 12 hours to obtain a flexible asymmetric composite thermal conductive film with a mass ratio of polyvinyl alcohol, graphene oxide, modifier and hexagonal boron nitride of 4.5:0.5:1:1.5.

[0071] Example 2

[0072] The difference between Example 2 and Example 1 is that the mass of hexagonal boron nitride in step (2) is 1.7 g, the volume of graphene oxide dispersion in step (3) is 30 mL, and finally a flexible asymmetric double-layer composite thermally conductive film is obtained in which the mass ratio of polyvinyl alcohol, graphene oxide, modifier and hexagonal boron nitride is 4.5:0.3:1:1.7.

[0073] Example 3

[0074] The difference between Example 3 and Example 1 is that the mass of hexagonal boron nitride in step (2) is 1.3 g, the volume of graphene oxide dispersion in step (3) is 70 mL, and finally a flexible asymmetric double-layer composite thermally conductive film is obtained in which the mass ratio of polyvinyl alcohol, graphene oxide, modifier and hexagonal boron nitride is 4.5:0.7:1:1.3.

[0075] Example 4

[0076] The difference between Example 4 and Example 1 is that the mass of hexagonal boron nitride in step (2) is 1.9 g, the volume of graphene oxide dispersion in step (3) is 10 mL, and finally a flexible asymmetric double-layer composite thermally conductive film is obtained in which the mass ratio of polyvinyl alcohol, graphene oxide, modifier and hexagonal boron nitride is 4.5:0.1:1:1.9.

[0077] Comparative Example 1

[0078] (1) 9 g of polyvinyl alcohol particles (degree of polymerization 1700 , alcoholysis degree is 88%) was dispersed in 90 mL of deionized water and magnetically stirred at room temperature until the solution was uniform and transparent, then 1 g of glycerol was added and magnetically stirred in a 90°C warm water bath for 2 h to obtain a polyvinyl alcohol solution;

[0079] (2) Pour the polyvinyl alcohol solution onto a stainless steel plate, and use an automatic coating machine to scrape the film. First, place it at a constant temperature of 40°C for 5 hours, and then place it in a constant temperature box at 60°C to dry for 12 hours to obtain a polyvinyl alcohol film. The filler content in this film is 0.

[0080] Comparative Example 2

[0081] (1) 9 g of polyvinyl alcohol particles (degree of polymerization: 1700, degree of alcoholysis: 88%) were dispersed in 90 mL of deionized water and magnetically stirred at room temperature until the solution was uniform and transparent. Then, 1 g of glycerol was added and magnetically stirred in a 90° C. warm water bath for 2 h to obtain a polyvinyl alcohol solution;

[0082] (2) mixing 1.3 g of hexagonal boron nitride having a sheet thickness of 1 to 2 μm, 1 g of dodecyl glucoside, and 20 mL of deionized water under magnetic stirring at room temperature to obtain a dodecyl glucoside / hexagonal boron nitride mixed solution;

[0083] (3) 50 mL of the polyvinyl alcohol solution obtained in step (1) and the mixed solution obtained in step (2) were first dispersed under high-frequency ultrasound for 2 minutes, and then magnetically stirred at room temperature for 6 hours to mix them evenly to obtain a polyvinyl alcohol / dodecyl glucoside / hexagonal boron nitride mixed solution;

[0084] (5) The polyvinyl alcohol / dodecyl glucoside / hexagonal boron nitride mixed solution is poured onto a stainless steel plate, and a film is scraped using an automatic coating machine at room temperature. The film is first allowed to stand at a constant temperature of 40° C. for 5 h, and then placed in a constant temperature box at 60° C. to dry for 12 h, thereby obtaining a flexible asymmetric composite thermal conductive film having a mass ratio of polyvinyl alcohol, modifier and hexagonal boron nitride of 4.5:1:1.3.

[0085] Comparative Example 3

[0086] (1) 9 g of polyvinyl alcohol particles (degree of polymerization: 1700, degree of alcoholysis: 88%) were dispersed in 90 mL of deionized water and magnetically stirred at room temperature until the solution was uniform and transparent. Then, 1 g of glycerol was added and magnetically stirred in a 90° C. warm water bath for 2 h to obtain a polyvinyl alcohol solution;

[0087] (2) dispersing 70 mL of a graphene oxide dispersion having a mass concentration of 1.0 wt% under high-frequency ultrasound for 30 min, mixing it with the polyvinyl alcohol solution obtained in step (1), and then magnetically stirring it at room temperature for 6 h to obtain a uniformly dispersed polyvinyl alcohol / graphene oxide mixed solution;

[0088] (3) The polyvinyl alcohol / graphene oxide mixed solution is poured onto a stainless steel plate, and a film is scraped using an automatic coating machine at room temperature. The film is first allowed to stand at a constant temperature of 40°C for 5 hours, and then placed in a constant temperature box at 60°C for drying for 12 hours to obtain a flexible asymmetric composite thermal conductive film with a mass ratio of polyvinyl alcohol to graphene oxide of 4.5:0.7.

[0089] Comparative Example 4

[0090] The difference between Example 4 and Example 1 is that the mass of hexagonal boron nitride in step (2) is 0.7 g, the volume of graphene oxide dispersion in step (3) is 130 mL, and finally a flexible asymmetric double-layer composite thermally conductive film with a mass ratio of polyvinyl alcohol, graphene oxide, modifier and hexagonal boron nitride of 4.5:1.3:1:0.7 is obtained.

[0091] Structural characterization

[0092] The SEM image of hexagonal boron nitride in Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that the boron nitride microplatelets after ultrasonic dispersion have irregular hexagons.

[0093] The digital images and SEM images of the upper and lower surfaces of the flexible asymmetric composite thermal conductive film obtained in Example 1 are as follows: Figure 2 As shown by Figure 2 It can be seen that there is an obvious difference in color between the upper and lower surfaces of the composite film. The upper surface is brown in color and contains more graphene oxide, while the lower surface is white in color and contains more hexagonal boron nitride. There are obvious differences in color and microscopic morphology on both sides of the obtained composite thermal conductive film.

[0094] The cross-sectional SEM image of the flexible asymmetric composite thermally conductive film obtained in Example 1 is as follows: Figure 3 As shown by Figure 3 It can be seen that there are obvious differences between the upper and lower surfaces of the composite film, and more hexagonal boron nitride is deposited on the lower surface of the composite film.

[0095] The flexibility of the flexible asymmetric composite thermal conductive film obtained in Example 1 is shown in the figure below: Figure 4 As shown by Figure 4 It can be seen that during the curling and folding process of the flexible asymmetric composite thermally conductive film obtained by the present invention, the surface of the film remains smooth and flat without any cracks, indicating that the film prepared by the present invention has good flexibility and shows great potential in the application of thermal management of flexible electronic devices.

[0096] The surface SEM image of the flexible asymmetric composite thermal conductive film obtained in Example 1 after etching is as follows: Figure 5 As shown by Figure 5 It can be seen that the surface polymer is etched away and the fillers in the composite material are exposed.

[0097] Performance Testing

[0098] The thermal conductivity of the films obtained in Examples 1 to 4 and the comparative example was tested using a transient method and a Netzsch LFA447 instrument.

[0099] The thermal conductivity of the graphene oxide surface of the composite thin film obtained in Examples 1 to 4 and Comparative Examples 1 to 4 is shown in FIG. Figure 6 As shown, the thermal conductivity diagrams of the boron nitride surfaces of the composite thin films obtained in Examples 1 to 4 and Comparative Examples 1 to 4 are as follows Figure 7 As shown. Figure 6 and Figure 7 It can be seen that the thermal conductivity of the composite film has been greatly improved. When the mass ratio of polyvinyl alcohol, graphene oxide, modifier and hexagonal boron nitride is 4.5:0.5:1:1.5, the thermal conductivity of the graphene oxide surface of the composite film reaches a maximum value of 10.07 W·m -1 ·K -1 , compared with 0.41 W·m -1 ·K -1 The thermal conductivity of the boron nitride surface has increased by 2356% to a maximum of 11.09 W·m -1 ·K -1 , compared with 0.41 W·m -1 ·K -1 It has increased by 2605%, greatly expanding the application scope of polymer materials in the field of thermal management.

[0100] The thermal conductivity of the graphene oxide surface and the boron nitride surface of the composite film obtained in Example 3 after reduction is as follows Figure 8 As shown; the surface resistance of the graphene oxide surface and the boron nitride surface of the obtained composite film after reduction is as shown Fig. 9 As shown. Figure 8 , 9 It can be seen that after reduction, the asymmetry of the two sides of the composite film is more obvious.

[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A flexible asymmetric composite thermally conductive film comprising the following components in parts by weight: The total mass content of the graphene oxide and hexagonal boron nitride in the flexible asymmetric composite thermal conductive film is 10-30%; The organic molecule modifier is one or more of tannic acid, dodecyl glucoside and dopamine; The method for preparing the flexible asymmetric composite thermally conductive film comprises the following steps: Mixing polyvinyl alcohol, glycerol and water to obtain a polyvinyl alcohol solution; Mixing hexagonal boron nitride, an organic molecular modifier and water to obtain a modifier / hexagonal boron nitride mixed solution; Mixing the graphene oxide dispersion with the modifier / hexagonal boron nitride mixed solution to obtain a graphene oxide / modifier / hexagonal boron nitride mixed solution; The polyvinyl alcohol solution and the graphene oxide / modifier / hexagonal boron nitride mixed solution are mixed to obtain a film-forming solution; Scraping the film-forming liquid on the surface of the substrate, leaving the obtained wet film to stand and heat to dry, to obtain a flexible asymmetric composite thermally conductive film; The mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 7-10%; The mass concentration of hexagonal boron nitride in the modifier / hexagonal boron nitride mixed solution is 55-67%; The mass concentration of the graphene oxide dispersion is 0.7-1.6%; The scraping speed is 160-220 mm / s; the static temperature is 25-40° C., and the time is 1-2 hours; The heating and drying comprises a first heating stage and a second heating stage which are carried out sequentially. The temperature of the first heating stage is 25-40° C. and the time is 2-5 hours. The temperature of the second heating stage is 60-80° C. and the time is 8-12 hours.

2. The flexible asymmetric composite thermally conductive film according to claim 1, characterized in that: The polymerization degree of the polyvinyl alcohol is 1500-2400, and the alcoholysis degree is 77-99%.

3. The flexible asymmetric composite thermally conductive film according to claim 1 or 2, characterized in that: The graphene oxide sheet has a thickness of 0.8 to 1 nm; The hexagonal boron nitride has a sheet diameter of 1 to 2 μm and a sheet thickness of 1 to 2 nm.

4. The flexible asymmetric composite thermally conductive film according to claim 1, characterized in that: The thickness of the flexible asymmetric composite thermally conductive film is 30-120 μm.

5. The method for preparing the flexible asymmetric composite thermally conductive film according to any one of claims 1 to 4, comprising the following steps: Mixing polyvinyl alcohol, glycerol and water to obtain a polyvinyl alcohol solution; Mixing hexagonal boron nitride, an organic molecular modifier and water to obtain a modifier / hexagonal boron nitride mixed solution; Mixing the graphene oxide dispersion with the modifier / hexagonal boron nitride mixed solution to obtain a graphene oxide / modifier / hexagonal boron nitride mixed solution; The polyvinyl alcohol solution and the graphene oxide / modifier / hexagonal boron nitride mixed solution are mixed to obtain a film-forming solution; Scraping the film-forming liquid on the surface of the substrate, leaving the obtained wet film to stand and heat to dry, to obtain a flexible asymmetric composite thermally conductive film; The mass concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 7-10%; The mass concentration of hexagonal boron nitride in the modifier / hexagonal boron nitride mixed solution is 55-67%; The mass concentration of the graphene oxide dispersion is 0.7-1.6%; The scraping speed is 160-220 mm / s; the static temperature is 25-40° C., and the time is 1-2 hours; The heating and drying comprises a first heating stage and a second heating stage which are carried out sequentially. The temperature of the first heating stage is 25-40° C. and the time is 2-5 hours. The temperature of the second heating stage is 60-80° C. and the time is 8-12 hours.

6. Use of the flexible asymmetric composite thermally conductive film according to any one of claims 1 to 4 or the flexible asymmetric composite thermally conductive film prepared by the preparation method according to claim 5 in flexible electronic devices.

Citation Information

Patent Citations

  • Hexagonal boron nitride / graphene oxide composite adsorption material and preparation method thereof

    CN103480329A

  • Boron nitride doped composite material and preparation method and application thereof

    CN105349114A